ChemInform Abstract: Defects and Disorder in Metal Organic Frameworks. Issue 16 (March 2016) - Cheetham, Anthony K.; Bennett, Thomas D.; Coudert, Francois‐Xavier; Goodwin, Andrew L.
Abstract: Review: 75 refs.